Pharmacological issues concerning olaparib capsule and tablet formulations in treating ovarian cancer: Are they really the same drug?. (June 2020) - Perego, Gianluca; Nozza, Renata; Oggionni, Emanuela; Cabiddu, Mary; Scolari, Cinzia; Omati, Elena; Castelli, Emanuela A; Petrelli, Fausto
Olaparib is a first-in-class PARP inhibitor that has demonstrated efficacy as maintenance therapy in patients with ovarian cancer. It has been approved as a capsule formulation and after the publication of data from SOLO2 study became available also as tablet formulation. Due to different pharmacokinetic properties, these different formulations cannot be considered bioequivalent nor interchangeable. The tablet formulation has improved bioavailability, reducing pill burden and offering a more convenient dosage regimen. Furthermore, olaparib tablet formulation had a manageable tolerability profile if compared to capsule one, with most of adverse events of mild or moderate severity. Under this light, olaparib tablet formulation is a useful maintenance strategy for recurrent, platinum-sensitive ovarian cancer, providing a more convenient dosing option than the capsule formulation.